Random response time of thin avalanche photodiodes - You, A. H.; Ong, D. S. (2004)
The avalanche built-up time using random response time model for avalanche photodiode (APD) is presented. A random response time model considers the randomness of times at which the primary and secondary carriers exit the multiplication region. The dead-space effect is included in our model to demonstrate its effect on response time of APDs especially for the thin devices. Our results show that feedback impact ionisation process and dead-space prolong the response time in APDs. The time response of homojunction InP p(+)-i-n(+) diodes with the multiplication region of 0.281, 0.582 and 1.243 mum are calculated.